Towards an ethics perspective on the rational structure tradition of organisational communication - Colin Chasi; Gideon de Wet (Communicare)
The rational structure tradition of organisational communication is much referenced in academic literature. The article outlines some key characteristics of this tradition. Some important theorists to have contributed to this tradition include the great sociologist, Max Weber; the great champion of scientific management, Fredrerick Taylor; and Luther Gulick, the champion of the division and coordination of work. The MacDonaldised organisation is used to illustrate, not to evidence, one form of organisation that has taken key aspects of the rational structure tradition to a fatal end. This article attempts to overview this tradition and thereby to contribute an ethics perspective focusing on the issue of the denial of the individual.